Rancang Bangun Pengenalan Modul Sensor dengan Konfigurasi Otomatis Berbasis Komunikasi I2C - Nicho Ferdiansyah Kusna; Sabriansyah Rizqika Akbar; Dahnial Syauqy (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Wireless Sensor Network is one of the many technologies currently used in various fields. But in fact to be able to make a WSN system can work requires a lot of time, experience and also sufficient knowledge. It is difficult to configure a node to work properly. In order for the sensor node can be used alone the process to be traversed quite complicated, starting from the arrangement of the circuit, wiring, programming and others. Solution to this problem is by applying a Modular WSN system where part of the node is separated into specific modules by type and usability, the module type is divided into core module (controller device), communication module and sensor module. In the existing module itself applied Plug and Play system so that each module can be directly used without having to go through any configuration process. In this study only focuses on the sensor module where the sensor module consists of several different types of sensors. The sensor modules that the PnP system has implemented can be directly used when connected to the controller. The process of detection and identification process is done by utilizing serial communication I2C (Inter Integrated Circuit). From the results of several tests conducted known that the process of detection, data transmission and also the selection of active modules successfully done without experiencing any constraints.